AN ANALYSIS OF ID AND EGO NOVEL “A TALE OF TWO CITIES” BY CHARLES DICKENS - Romanna; Gaguk Rudianto (English Study Program University of Pasir Pengaraian, 2020)
This study aims to describe the id and ego of the characters in the novel A Tale of Two Cities by Charles Dickens using the approach of psychological approach. This type of research is a qualitative descriptive study and the data obtained from this study produce a psychological analysis in the Charles Dickens novel entitled